Anesthetic and critical care challenges in massive chyle leak following robotic surgery: a special case report - Hariharan, Uma; Choudhary, Itee; Bhargava, Ajay Kumar (Journal of Society of Anesthesiologists of Nepal, 2015)
A unique case report is hereby presented which entails the multi-modality management of a very rare complication of modern minimally-invasive robotic surgery. Chyle leak can be an extremely challenging problem following certain surgeries, especially in cancer patients. Medical, nutritional and/or surgical management is required to control the leak. Prolonged massive chyle leaks which do not respond to conservative management require surgical intervention. Retroperitoneal lymph node dissection is a complex procedure undertaken for lymph node clearance in germ cell tumors after primary radical surgery. Robotic surgeries have revolutionized the field of minimally invasive operations. A patient who underwent robotic nerve sparing retroperitoneal lymph node dissection for non-seminomatous germ cell tumor of the right testis, post-chemotherapy, developed a continuous large volume chylous ascites, presenting with electrolyte imbalances and hypotension. Exploratory laparotomy in the operation theatre was required for sealing the chyle leak after failure of medical and nutritional management in the intensive care unit. The main take-away message is that refractory chyle leak can occur in retroperitoneal surgeries requiring multidisciplinary management. Careful coordinated action between critical care, oncological, anesthesia and surgical teams is mandatory for a favourable outcome. Familiarity with the nuances of robotic surgery and eternal vigilance are the keys to successful conduction of complex robotic procedures. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 73-76